KAITAN HUKUM ISLAM DENGAN PERKEMBANGAN ILMU PENGETAHUAN DAN TEKNOLOGI - U., M. Sabir (Hunafa: Jurnal Studia Islamika, 2007)
During the prophet’s life, all legal problems  would be returned to him. Then, he would  make a decision  on those problems. It is different from  our contemporary era since the prophet has passed away  while there are  some problems brought about by the development of science and of technology. For example,  transplantation and insemination, both of which should be discussed by Muslim scholars to determine   whether or not both are permitted by Islam. If  both are banned or are permitted, then what  are the conditions for banning  or  permitting them. Within this context, this article elaborates the relationship between Islamic law and the development of science and of technology.Kata Kunci : hukum Islam, ilmu pengetahuan, teknologi